Negotiating the risks of computed tomography in primary care - Moreland, J-A; Gleeson, FV; Nicholson, BD (Royal College of General Practitioners, 2020)
Computed tomography (CT) is one of the most frequently used imaging modalities. Over 5 million scans were performed in the UK in 2017/2018, a 6.9% increase from 2016/2017. One in ten scans performed for initial cancer investigations were referred directly from GPs.1 Versatility of scanners, an ageing population, patient knowledge, and improved access are some factors that have led to an increase in demand; however, there is regional variation in direct-access radiology for GPs in the UK. When GPs have direct access to cancer investigations, they diagnose cancer in a similar proportion of patients to specialists with the same test. The risks of ionising radiation from CT conflict with the demand for earlier cancer diagnosis creating a risk/benefit dilemma. GPs who frequently refer to CT may come under pressure from commissioners for their use of radiology, but if slow to refer they may be criticised for late diagnoses following repeat patient attendances.